PENGARUH PENGGUNAAN MEDIA VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PAI KELAS IV SDN 19 PULAI - Ekanala, Roy; Zen, Zelhendri; Syafril; Pratiwi, Rahmi (Sindoro: Cendikia Pendidikan, 2024)
The problems found in the field based on observations made in class IV of SD Negeri 19 Pulai Kota Padang, it appears that students do not understand PAI learning material, this is caused by the textbook media which does not describe the learning material and one of the media that can help is the teacher using learning video media in the learning process of PAI subjects. This research aims to reveal the effect of using video learning media on PAI learning outcomes for class IV students at SD Negeri 19 Pulai. This research uses quantitative research methods in the form of quasi-experiment. The population of this study was class IV of SD Negeri 19 Pulai, totaling 62 students. Sampling used total sampling technology, that is, all students were taken as samples, namely 31 students in the experimental class and 31 students in the control class. Data collection techniques use test techniques. From the research results, the experimental group's average value was 80.403, which was higher than the control group's average value of 74.67. From the t test analysis, it was obtained that tcount > ttable = 2.99 > 2.00, meaning that there was a significant difference in learning outcome scores at the α = 0.05 level. So it can be concluded that the use of learning video media influences PAI learning outcomes for class IV students at SDN 19 Pulai.